Dressing code compliance in academic libraries: a case study of Igbindion University Library, Okada (2003)
This paper evaluates the enforcement of dressing code in Igbinedion University Library, Okada. It reveals the effect on readers’ concentration. Also, the justification for its introduction in a private initiative library was emphasized. The paper identifies ways of demanding compliance by the Librarians considering likely position posture of the affected students while suggestions were made to help reduce, if not curb indecent dressing that has eaten deep into the fabrics of the nations academic sector.